Synchronous degradation and decolorization of colored poly(ethylene terephthalate) fabrics for the synthesis of high purity terephthalic acid. (15th September 2022) - Li, Yanyan; Yi, Hongling; Li, Mengjuan; Ge, Mingqiao; Yao, Donggang
Abstract: The grand challenge in chemical recycling of colored poly(ethylene terephthalate) (PET) wastes is to achieve cost-effective decolorization and purification of products. In the present work, an effective method combining hydrolysis, reactive processing and decoloration was developed to convert colored PET fabrics into high purity terephthalic acid (TPAca ). Identification of intermediates and quantification of products were carried out by a range of characterizations, including SEM, EDS, TGA, FTIR, XRD, NMR and GPC. The color removal efficiency and selectivity and yield of the synthesized TPAca were calculated with the assistance of UV–vis, K/S values and chromaticity diagram to evaluate the viability of the method. It is found that disperse dyes with different structures (azo and anthraquinone) can be decolorized simultaneously with PET degradation under the joint effects of sublimation, pyrolysis and hydrolysis. In the process, calcium terephthalate (CaTP) acts as an essential medium to store and protect the synthesized TPAca . Overall, the purity of the obtained TPAca is comparable to that of commercial TPA. The monomer yield (88.51%) and decolorization rate (94.22–97.65%) are higher than TPAna produced from traditional hydrolysis. Along with future development towards sustainability, we anticipate that this method could be utilized as a basis for recycling and upcycling of complex colored PET wastes at an industrial level. Graphical abstract: Image 1 Highlights: Propose an enhanced hydrolysis route assisted by reactive processing for PET. CaTP provides a venue to store and protect the synthesized TPA in decolorization. The recycling route is applicable to waste PET colored by different disperse dyes. The TPA yield (88.51%) and decolorization rate (94.22–97.65%) are competitive. Realize simultaneous decomposition and decolorization of colored PET.